Dynamic Wetting Behaviors of Water Droplets on Surfaces with Dual Structures at the Nanoscale. (August 2020) - Kwon, Tae Woo; Lee, Kwang Ho; Seo, Young Min; Jang, Joonkyung; Ha, Man Yeong
Highlights: Molecular dynamics simulations were carried out to investigate the dynamic wetting behaviors of water droplets on surfaces with dual structures at the nanoscale. The effects of the surface characteristic energy, pillar height, and applied force on the dynamic wetting behavior were considered. The dynamic behaviors of water droplets could be classified into four groups according to their dynamic shapes. The dual structures make the surface more hydrophobic in the dynamic state, as well as the static state, compared to the single structures. Abstract: Molecular dynamics simulations were carried out to investigate the static and dynamic wetting behaviors of water droplets on surfaces with single and dual structures at the nanoscale. The effects of the surface characteristic energy, pillar height, and applied force on the dynamic wetting behavior were considered in this study. The dual structures were constructed by attaching small minor bump textures to the main pillar structures. The dynamic behaviors of water droplets could be classified into four different groups according to their dynamic shapes. The dynamic wetting behaviors were quantitatively evaluated according to the contact angle hysteresis and the ratio of water molecules penetrating into the gaps between pillars. As a result, the dual structures make the surface more hydrophobic in the dynamic state, as well as the static state, compared to the single structures.